Effect of mechanical cycling on screw torque in external hexagon implants with and without platform switching - Carvalho, Bruno Andrade Cantharino De; Vedovatto, Eduardo; Carvalho, Paulo Sérgio Perri de [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Falcón-antenucci, Rosse Mary [UNESP] (Fundação Odontológica de Ribeirão Preto, 2015)
This in vitro study evaluated the effect of mechanical cycling on the torque of retaining screw in external hexagon implants with platform switching (PS), regular platform (RP) and wide platform (WP). A total of 30 specimens were equally divided into 3 groups: PS, PR and WP. Each specimen was prepared with implants: 3.75 x 10 mm for RP group and 5.0x10 mm for PS and WP groups and its respective abutment with 32 Ncm torque. All groups were subjected to 106 cycles with 100 N (corresponding to about 40 months of chewing). The results were obtained with the reverse torque of each specimen and data were evaluated using ANOVA and Tukey test (p<0.05). The PS group showed statistically significant difference in screw removal torque (30.06±5.42) compared with RP (23.75±2.76) and WP (21.32±3.53) (p<0.05) groups; the RP and WP groups showed no statistically significant difference between them. It was concluded that the PS group showed higher reverse torque value, suggesting lower susceptibility of the abutment screw loosening.

Este estudo in vitro avaliou o efeito da ciclagem mecânica no torque dos parafusos de retenção em implantes de hexágono externo com plataforma switching (PS), plataforma regular (RP) e plataforma larga (WP). Foram utilizados 30 corpos de prova divididos em 3 grupos equitativamente: PS, RP e WP. Cada corpo de prova foi preparado com implantes: 3,75x10 mm para o grupo RP e 5,0x10 mm para os grupos PS e WP, e seu respectivo abutment com o torque de 32 Ncm. Todos os grupos foram submetidos a 106 ciclos com 100 N de força (o que corresponde a aproximadamente 40 meses de mastigação). Os resultados foram obtidos com o torque reverso de cada espécime e os dados foram avaliados com ANOVA comparado com o teste de Tukey (p<0,05). O grupo PS apresentou diferença estatisticamente significante no torque de remoção do parafuso (30,06±5,42) comparado com os grupos RP (23,75±2,76) e WP (21,32±3,53) (p<0,05); os grupos RP e WP não apresentaram diferença estatisticamente significante entre si. Concluiu-se que o grupo PS apresentou maior valor de torque reverso sugerindo menor susceptibilidade de afrouxamento do parafuso de fixação do abutment.
Keywords: Dental implants; Platform switching; Reverse torque; Mechanical cycling